PENGEMBANGAN MEDIA ELEKTRONIK ULAR TANGGA MATERI UNGKAPAN KATA BERMAKNA DENOTATIF DAN KONOTATIF KELAS VI SD NEGERI 193 PEKANBARU - Dwi Chintiya, Marina; Dafit, Febrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study was motivated by student’s low interest in learning due to use of learning media that lacked variety and still relied on conventional teaching methods. The purpose of this study was to describe the development of an Electronic Snakes and Ladders learning media for the topic of Denotative and Connotative Expressions. This study employed the Research and Development (R&D) method using the ADDIE model, focusing on the Analysis, Design and Development stages. The results showed that: (1) The Electronic Snakes and Ladders learning media was categorized as highly valid based on expert validation results, with a score of 82.95% from the material expert, 95% from the language espert, and 96.25% from media espert; (2)The teacher response assessment reached 97.66%. The Electronic Snakes and Ladders learning media developed for the topic of denotative and connotative expressions received a “very good” category and was therefore considered highly suitable for use in the learning process.